Determining biologic width and its relevance in periodontics – a review - Deeksha Sain; Amitha Ramesh; Pranav Murthy; Karthika Nair; Ayush Gupta (Romanian Journal of Stomatology)
The length from the root surface of a tooth to the junctional epithelium and connective tissue attachment is termed as biological width (BW). It protects the tooth from diseases and infections by acting as a natural seal. On an average it is 2.04 mm. In clinical practice the BW is determined by periodontal probe. The calculation of BW can be done by several methods. An identification of BW breach is confirmed when the length is observed to be less than 2 mm at multiple locations or at a single location. When we are considering the prolonged health benefits of any restoration or a natural tooth, the health of the gingiva is of prime importance. An excess of BW breach leads to innumerable adverse effects, which are talked about in this review article. The article sheds light on BW in association to implants and conservative procedures and its evaluation clinically, and also a discussion about the procedures that can be used to rectify BW breaches in routine practice.